Optical Properties of Undoped and Indium-doped Tin Oxide Thin Films (Journal of Bangladesh Academy of Sciences, 2011)
Thin films of Tin Oxide (SnO2), having thickness of 200 nm, were formed on to glass substrates by thermal evaporation of high-purity SnO2 powder in vacuum at various substrate temperatures (TS), ranging between 25 and 200°C. SnO2 films with varying thickness were also prepared for a fixed TS = 100°C. Further, doping of SnO2 films with Indium (In) was accomplished through solid state diffusion process by successive deposition of SnO2 and In films and subsequent annealing at 200°C for 10 minutes. Both undoped and doped films were characterized optically by UV-VIS-NIR spectrophotometry in the photon wavelength ranging from 300 to 2500 nm. In the visible photon wavelength range, the average optical transmittance (T%) of the films with varying TS was found to be 85%. The maximum value of T % was found to be 89 % around the wavelength of 700nm. The variation of absorption coefficient with photon energy in the fundamental absorption region is the steepest for TS = 100°C. The sub-band gap (SBG) absorption is also minimum for this Ts. A fluctuating behavior of the band gap energy (Eg) with Ts is observed attaining the highest value of 3.59 eV for Ts = 100°C. The band gap energy increases with thickness but T% in the visible range decreases. The T% in the visible range varies inversely with indium doping, being highest for undoped films. The Eg increases upto 2 wt% In doping and gradually decreases for enhanced doping. It seems reasonable to conclude that In doping does not bring favorable optical characteristics. Undoped SnO2 films having thickness of 200 nm and formed at substrate temperature of 100°C yield essential acceptable properties for photovoltaic applications.DOI: http://dx.doi.org/10.3329/jbas.v35i1.7975Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 99-111, 2011